English Learning through the Group Work for Learner - Yulia Nugrahini (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Language have several ways to study, especially English. There is a special way to study English, for example Group Work learner. Like the other activities, group work for learner in language is more likely to go well if it is properly planned. Group work as a media to learn language so group work must plan with properly guided. Planning requires an understanding of the principle that lies behind successful group work. After planned the group work for learner, we can apply the principle to a good preparation. There are the typical question for the teacher “How many people should there be in a group?”, “Is the best to have people/students of mixed ability/proficiency or equal ability/proficiency?” etc. the best answered is applying the principles. There are the 5 types of principles of group work: the combining arrangement, the cooperative arrangement, the superior-inferior arrangement, and the individual arrangement. If the principle is not applied, then the group work for learner will probably not go smoothly. Each the principle have advantage and disadvantage. So the goal of group work for learner help learning in the following ways: negotiation of input, new language item, fluency, communication strategies, and content.